Return variability in CARICOM equity markets - Watson, Patrick Kent ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Examines the validity of the Sharpe-Linter-Black Capital Asset Pricing Model (CAPM) to stocks traded on the Barbados, Jamaica and Trinidad & Tobago Stock Exchanges.